Pengaruh Kompetensi Aparatur Desa, Pemanfaatan Teknologi Informasi, dan Partisipasi Masyarakat terhadap Akuntabilitas Pengelolaan Dana Desa: Studi Empiris pada Nagari di Kabupaten Tanah Datar - Rahmawati, Rahmawati; Mulyani, Erly (Jurnal Eksplorasi Akuntansi, 2025)
The research aims to determine the influence of competency of apparatus, utilization of information technology and community participation on village fund management accountability (Empirical Study on Nagari in Tanah Datar Regency). The population used in this research was all nagari apparatus in Tanah Datar Regency, totalling 600 nagari apparatus from 75 nagari. The sampling technique uses a purposive sampling method. In determining the number of samples, Issac and Michael’s formula was use to obtain 234 apparatus on 30 nagari. This type of research is quantitative research. The data source in this research is primary data by distributing questionnaires to nagari official in Tanah Datar Regency. Data analysis uses multiple linear regression analysis. The result of this research show that competency of apparatus, utilization of information technology and community participation have a positive and significant effect on village fund management accountability.